2022
DOI: 10.1002/jbm.b.35133
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of periodontal tissue regeneration using a 3D‐printed carbon nanotube/chitosan/sodium alginate composite scaffold

Abstract: Periodontal disease is a common disease in the oral field, and many researchers are studying periodontal disease and try to find some biological scaffold materials to make periodontal tissue regenerative. In this study, we attempted to construct a carbon nanotube/chitosan/sodium alginate (CNT/CS/AL) ternary composite hydrogel and then prepare porous scaffold by 3D printing technology. Subsequently, characterizing the materials and testing the mechanical properties of the scaffold. Additionally, its effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…SA exhibited amorphous crystalline peaked at 13.56° and 21.87°. Similarly, the study supported the characteristic peaks of sodium alginate found at 14° and 22° [ 41 ]. The crystalline peaks of CS were weak and shifted when prepared the CS-TTO NEMs which was due to the deformation of the hydrogen bond in the polymer.…”
Section: Resultssupporting
confidence: 82%
“…SA exhibited amorphous crystalline peaked at 13.56° and 21.87°. Similarly, the study supported the characteristic peaks of sodium alginate found at 14° and 22° [ 41 ]. The crystalline peaks of CS were weak and shifted when prepared the CS-TTO NEMs which was due to the deformation of the hydrogen bond in the polymer.…”
Section: Resultssupporting
confidence: 82%
“…Most recently, composite antimicrobial hydrogels consisting of carbon nanotube, chitosan, and sodium alginate were developed for the treatment of periodontitis. 49 Their cytocompatibility was confirmed using human periodontal ligament cells. Also, these hydrogels exerted an antimicrobial action against Porphyromonas gingivalis .…”
Section: Challenges and Future Prospectsmentioning
confidence: 96%
“…Coming closer to the present, 3D-printed antimicrobial hydrogels have emerged in periodontics. 49 During the last few years, antimicrobial hydrogels have only been reviewed from a broad spectrum of applications. 50,51 The engineering of antimicrobial hydrogels exclusively for endodontics and periodontics has not been reported elsewhere.…”
Section: Reviewmentioning
confidence: 99%
“…In addition, various growth agents can be coupled with 3D printed scaffolds to aid in the regeneration of periodontal tissues. In addition to the internal microstructure [84], 3D printing with layer-by-layer deposition enables the creation of a custom-designed scaffold in a shape and size that corresponds to the anatomic shape of each periodontal lesion [85]. Despite the limited number of publications to date, the use of 3D printing for periodontal regeneration looks to be on the rise.…”
Section: D Printed Scaffoldsmentioning
confidence: 99%